2022
DOI: 10.5194/gmd-2021-434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analog Data Assimilation for the Selection of Suitable General Circulation Models

Abstract: Abstract. Data assimilation is a relevant framework to merge a dynamical model with noisy observations. When various models are in competition, the question is to find the model that best matches the observations. This matching can be measured by using the model evidence, defined by the likelihood of the observations given the model. This study explores the performance of model selection based on model evidence computed using data-driven data assimilation, where dynamical models are emulated using machine lear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The forecast takes into account the regression uncertainty (assumed Gaussian) which is a robust estimate of the model error. When the catalog is large enough (to approximately cover the full state space), it has been shown that AnDA performs as well as DA (Lguensat et al 2017). Ruiz et al 2022 have recently shown, using different idealized dynamical models, that CME can be robustly estimated using AnDA.…”
Section: Evaluating the Local Performance Of A Dynamical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The forecast takes into account the regression uncertainty (assumed Gaussian) which is a robust estimate of the model error. When the catalog is large enough (to approximately cover the full state space), it has been shown that AnDA performs as well as DA (Lguensat et al 2017). Ruiz et al 2022 have recently shown, using different idealized dynamical models, that CME can be robustly estimated using AnDA.…”
Section: Evaluating the Local Performance Of A Dynamical Modelmentioning
confidence: 99%
“…In this study, we evaluate the performance of competing models based on their ability to reproduce short-term dynamics of the system described by observed sequences. To achieve this, a data-driven approach is adopted within a data assimilation framework (Ruiz et al 2022). One of the main advantage is the use of already existing simulations to produce free-model probabilistic forecasts (i.e.…”
Section: Introductionmentioning
confidence: 99%